Going Mobile: How Mobile Personal Health Records Can Improve Health Care During Emergencies - Bouri, Nidhi; Ravi, Sanjana (JMIR Publications, 2014)
Personal health records (PHRs), in contrast to electronic health records (EHRs) or electronic medical records (EMRs), are health records in which data are accessible to patients and not just providers. In recent years, many systems have enabled PHRs to be available in a mobile format. Mobile PHRs (mPHRs) allow patients to access health information via the Internet or telecommunication devices, such as mobile phones, personal digital assistants, and tablet computers. mPHRs have the potential to help patients and providers identify medical conditions and prescriptions from numerous locations, which may minimize medical errors and identify improvements to health behaviors during emergencies, when patients present to a new provider, or EHRs are not accessible. Despite their benefits, numerous challenges inhibit the adoption and further development of mPHRs, including integration into overall health technology infrastructure and legal and security concerns. This paper identifies the benefits of mPHRs during emergencies and the remaining challenges impeding full adoption and use, and provides recommendations to federal agencies to enhance support and use of mPHRs.